2002
DOI: 10.1021/la020405s
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Neutron Scattering Study of the Effect of Pressure on AOT−n-Octane−Water Mesophases and the Effect of α-Chymotrypsin Incorporation

Abstract: It has been demonstrated that the application of hydrostatic pressure to enzymes placed in surfactant "nanocontainers", such as reversed micelles, can bring additional advantages for both increasing the enzyme stability and modulating the enzyme activity. The effects of pressure on the structural properties of the surfactant matrices are essentially unknown, however. In this paper, small-angle neutron scattering experiments were carried out to study the effect of pressure on the structure of AOT-n-octane-water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…On the other hand, it was reported that the anionic surfactant NaAOT can be made to form micelles with diverse shapes by adjusting experimental parameters. [33][34][35][36] The self-assembled AOT À layers at the interface of water and oil could act as template for growing ZnO. The hydrophilic head of AOT À can form an anionic surface exposed to water, and thus Zn 2+ cations can directly attach to the negatively charged AOT À template to initiate the first layer of crystal growth [Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it was reported that the anionic surfactant NaAOT can be made to form micelles with diverse shapes by adjusting experimental parameters. [33][34][35][36] The self-assembled AOT À layers at the interface of water and oil could act as template for growing ZnO. The hydrophilic head of AOT À can form an anionic surface exposed to water, and thus Zn 2+ cations can directly attach to the negatively charged AOT À template to initiate the first layer of crystal growth [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it was reported that the anionic surfactant NaAOT can be made to form micelles with diverse shapes by adjusting experimental parameters. [33][34][35][36] The self-assembled AOT À layers at the interface of water and oil could act as template for growing ZnO Fast growth along h21 1 0i results in the formation of a hexagonal disk (Figure 5 a). Slight bending of the selfassembled AOT À monolayer makes it possible to accommodate local strain in the disk by formation of small-angle grain boundaries closely parallel to {21 1 0}.…”
mentioning
confidence: 99%
“…The large polar surface is generally energetically unfavorable unless the surface charge is compensated by a passivation agent. On the other hand, it was reported that the anionic surfactant NaAOT can be made to form micelles with diverse shapes by adjusting experimental parameters 3336. The self‐assembled AOT − layers at the interface of water and oil could act as template for growing ZnO.…”
mentioning
confidence: 99%
“…In the case of AOT reverse micelles, the particle size distribution is narrow, i.e. uniformed micelles of equal size are formed at each surfactant hydration degree, (28,29). The inner cavity radius of the micelle, r m , expressed in Å, was shown to conform to the empirical equation (27), r m ϭ 1.5w 0 ϩ 4 (Eq.…”
Section: Methodsmentioning
confidence: 98%
“…which holds for all enzyme-containing reverse AOT micellar systems studied thus far (29). In a typical kinetic experiment, a solution of LADH, NADH, and DCPIP in 50 mM Tris-HCl buffer, pH 7.5, or in 25 mM citrate buffer, pH 5.8, was solubilized by intensive shaking in a solution of 0.1 M AOT in octane.…”
Section: Methodsmentioning
confidence: 99%